Molecule-like and lattice vibrations in metal clusters. Issue 22 (26th May 2022) - Ramankutty, Krishnadas Kumaranchira; Yang, Huayan; Baghdasaryan, Ani; Teyssier, Jeremie; Nicu, Valentin Paul; Buergi, Thomas
Abstract : Low frequency Raman spectra of a series of atomically precise gold, silver and alloy clusters are presented. The spectra are characteristic for each cluster and show a systematic change upon alloying. Abstract : We report distinct molecule-like and lattice (breathing) vibrational signatures of atomically precise, ligand-protected metal clusters using low-temperature Raman spectroscopy. Our measurements provide fingerprint Raman spectra of a series of noble metal clusters, namely, Au25 (SR)18, Ag25 (SR)18, Ag24 Au1 (SR)18, Ag29 (S2 R)12 and Ag44 (SR)30 (–SR = alkyl/arylthiolate, –S2 R = dithiolate). Distinct, well-defined, low-frequency Raman bands of these clusters result from the vibrations of their metal cores whereas the higher-frequency bands reflect the structure of the metal–ligand interface. We observe a distinct breathing vibrational mode for each of these clusters. Detailed analyses of the bands are presented in the light of DFT calculations. These vibrational signatures change systematically when the metal atoms and/or the ligands are changed. Most importantly, our results show that the physical, lattice dynamics model alone cannot completely describe the vibrational properties of ligand-protected metal clusters. We show that low-frequency Raman spectroscopy is a powerful tool to understand the vibrational dynamics of atomically precise, molecule-like particles of other materials such as molecular nanocarbons, quantum dots, and perovskites.